2021
DOI: 10.1038/s41467-021-21945-3
|View full text |Cite
|
Sign up to set email alerts
|

A molecular photosensitizer achieves a Voc of 1.24 V enabling highly efficient and stable dye-sensitized solar cells with copper(II/I)-based electrolyte

Abstract: To develop photosensitizers with high open-circuit photovoltage (Voc) is a crucial strategy to enhance the power conversion efficiency (PCE) of co-sensitized solar cells. Here, we show a judiciously tailored organic photosensitizer, coded MS5, featuring the bulky donor N-(2’,4’-bis(dodecyloxy)-[1,1’-biphenyl]-4-yl)-2’,4’-bis(dodecyloxy)-N-phenyl-[1,1’-biphenyl]-4-amine and the electron acceptor 4-(benzo[c][1,2,5]thiadiazol-4-yl)benzoic acid. Employing MS5 with a copper (II/I) electrolyte enables a dye-sensitiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
300
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(304 citation statements)
references
References 41 publications
4
300
0
Order By: Relevance
“…94 Very recently, Grätzel et al reported the highest efficiency of 34.5% under 1000 lux for DSSCs with copper(II/I)-based electrolyte, indicating that this type of photovoltaics still occupies a leading position in the eld of IPVs. 95 In 2019, Liu et al summarized the PCE, V oc , and bandgap of various types of IPVs, such as Si thin-lm, perovskite, GaAs, InGaP, DSSCs, and OPVs based IPVs (Fig. 2c).…”
Section: Research Progress Of Ipvsmentioning
confidence: 99%
“…94 Very recently, Grätzel et al reported the highest efficiency of 34.5% under 1000 lux for DSSCs with copper(II/I)-based electrolyte, indicating that this type of photovoltaics still occupies a leading position in the eld of IPVs. 95 In 2019, Liu et al summarized the PCE, V oc , and bandgap of various types of IPVs, such as Si thin-lm, perovskite, GaAs, InGaP, DSSCs, and OPVs based IPVs (Fig. 2c).…”
Section: Research Progress Of Ipvsmentioning
confidence: 99%
“…The ever‐increasing energy demands combined with climate and environmental concerns have motivated our society to find alternative renewable energy sources [1, 2] . Dye‐sensitized solar cells (DSCs) have attracted widespread research attention as one of the most promising next‐generation solar cell technologies over the past three decades, because of their simplicity of fabrication, aesthetic design characteristics, and excellent performance especially for diffuse and low light applications [3–14] …”
Section: Introductionmentioning
confidence: 99%
“…Dye-sensitized solar cells (DSSCs), for example, combine wide band-gap metal-oxide semiconductors with molecular photosensitizers to generate electricity from sunlight; however, in the past 25 years, power conversion efficiencies (PCE) have increased only slightly from 10% in 1997 1 to 13.5% in 2021. 2 Organic chromophores devoid of rare metals have supplanted traditional dyes in the recent record devices, which may also offer the opportunity to exceed existing limits by multiplying excitons. 3,4 Singlet fission represents one opportunity for exciton multiplication, 3 and understanding of the process in various molecular chromophores has advanced significantly over the past decade.…”
Section: Introductionmentioning
confidence: 99%
“… 1 ) to 13.5% in 2021. 2 Utilizing chromophores with exciton multiplication potential, such as singlet fission (SF) dyes, offers an opportunity to exceed conventional PCE limits. 3,4 Understanding of SF in various molecular chromophores has advanced significantly over the past decade.…”
Section: Introductionmentioning
confidence: 99%